Frogs Jump Forward: Semantic Knowledge Influences the Perception of Element Motion in the Ternus Display. (July 2015) - Hsu, Patty; T. Taylor, J. Eric; Pratt, Jay
The Ternus effect is a robust illusion of motion that produces element motion at short interstimulus intervals (ISIs; <50 ms) and group motion at longer ISIs (>50 ms). Previous research has shown that the nature of the stimuli (e.g., similarity, grouping), not just ISI, can influence the likelihood of perceiving element or group motion. We examined if semantic knowledge can also influence what type of illusory motion is perceived. In Experiment 1, we used a modified Ternus display with pictures of frogs in a jump-ready pose facing forwards or backwards to the direction of illusory motion. Participants perceived more element motion with the forward-facing frogs and more group motion with the backward-facing frogs. Experiment 2 tested whether this effect would still occur with line drawings of frogs, or if a more life-like image was necessary. Experiment 3 tested whether this effect was due to visual asymmetries inherent in the jumping pose. Experiment 4 tested whether frogs in a "non-jumping, " sedentary pose would replicate the original effect. These experiments elucidate the role of semantic knowledge in the Ternus effect. Prior knowledge of the movement of certain animate objects, in this case, frogs can also bias the perception of element or group motion.